Research on fabrication and sensing properties of fiber-coupled whispering gallery mode microsphere resonator - Zhang, Y.N. (2021)
In this paper, a fiber-coupled whispering gallery mode (WGM) microsphere resonator was fabricated with using a simple package scheme. The resonant properties of the WGM resonator are analyzed and their responses to bulk refractive index and temperature are theoretically and experimentally investigated. Experiment results show that the bulk refractive index sensitivity is about 20.49 nm/RIU with detection limit of 4.3× 10^{-4} RIU and very low temperature sensitivity of 7.38 pm/°C. Moreover, the WGM microsphere resonator is firstly used for acoustic intensity level sensing, and the sensitivity is about -1.9 pm/dB, which can enlarge the application field of the WGM sensor and can be used for noise monitoring to enhance environmental protection.